2017
DOI: 10.1007/s00246-017-1778-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Persistent Left Superior Vena Cava in the Normal Population and in Patients with Congenital Heart Diseases Detected Using Echocardiography

Abstract: Reports on the incidence of persistent left superior vena cava (PLSVC) in the normal population are limited to studies involving pacemaker implantation candidates and cadavers. The incidence in patients with congenital heart diseases (CHDs) is estimated to be higher than that in the normal population; however, the details are unclear. To investigate the incidence of PLSVC in the normal population and in patients with CHDs, subjects were examined prospectively using echocardiography. Normal subjects consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 9 publications
0
42
2
3
Order By: Relevance
“…Generally, the left common CV and the caudal part of the left superior CV will regress. If these veins do not regress, then they will persist as PLSVC [2,3,[8][9][10][11].…”
Section: Embryologymentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the left common CV and the caudal part of the left superior CV will regress. If these veins do not regress, then they will persist as PLSVC [2,3,[8][9][10][11].…”
Section: Embryologymentioning
confidence: 99%
“…Additionally, it is informed that 45% of patients with PLSVC in the antenatal period have accompanying heterotaxy [15]. In a study, DSVC is detected in nearly half of patients with heterotaxy [8]. Another study reported that 72% of heterotaxy patients with SVC anomaly have DSVC, while the remaining have IPLSVC [23].…”
Section: Plsvc and Heterotaxymentioning
confidence: 99%
“…Increased risk of coarctation of aorta (CoA) was noticed in up to 21% of fetuses with PLSVC ( 3 ) . The ratio of the incidence of PLSVC in CHD patients to that in the normal population was very high (over hundredfold) in CoA and DORV group ( 6 ) . There is a high prevalence of ventricular septal defect, atrial septal defect, endocardial cushion defect, cortriatriatum and tetralogy of Fallot in patients with PLSVC and agenesis of the right SVC ( 15 ) .…”
Section: Discussionmentioning
confidence: 91%
“…This is the most common variant of anomalous systemic venous return in adults ( 3 ) . PLSVC is observed in 0,21% of the general population and 4–8% of patients with congenital heart disease (CHD) ( 5 , 6 ) . There is no sex difference in the incidence of PLSVC ( 6 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of persistent left superior vena cava (PLSVC) is approximately 0.2%‐0.6% in the general population 1 and is higher in patients with congenital heart disease 2 . The PLSVC most commonly drains into the right atrium through an enlarged coronary sinus (CS) 3 .…”
Section: Introductionmentioning
confidence: 99%